2019
DOI: 10.3892/etm.2019.7850
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA MAFG‑AS1 promotes proliferation, migration and invasion of hepatocellular carcinoma cells through downregulation of miR‑6852

Abstract: Long noncoding RNAs (lncRNAs) have been shown to participate in the development and progression of a number of different types of cancer, including hepatocellular carcinoma (HCC). A recent report has indicated that lncRNA MAFG-antisense 1 (AS1) promotes colorectal cancer. However, the role of MAFG-AS1 in other types of cancer remains unclear. The aim of the present study was to examine the effect of lncRNA MAFG-AS1 in HCC. Based on The Cancer Genome Atlas database and reverse transcription-quantitative PCR res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…In addition, our func- tional experiments validated that compared with the control group, MAFG-AS1 silencing could significantly repress the proliferation, migration, and invasion of BLCA cells. The data suggest that, in BLCA, MAFG-AS1 exerts oncogenic function and is a promising therapy target, which is consistent with previous reports [10,11,[25][26][27]. miRNAs are endogenous small noncoding RNAs containing 18-25 nucleotides.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, our func- tional experiments validated that compared with the control group, MAFG-AS1 silencing could significantly repress the proliferation, migration, and invasion of BLCA cells. The data suggest that, in BLCA, MAFG-AS1 exerts oncogenic function and is a promising therapy target, which is consistent with previous reports [10,11,[25][26][27]. miRNAs are endogenous small noncoding RNAs containing 18-25 nucleotides.…”
Section: Discussionsupporting
confidence: 90%
“…According to previous reports, MAFG-AS1 is a cancerpromoting lncRNA that is involved in non-small cell carcinoma, hepatocellular carcinoma, gastric cancer, breast cancer, and colorectal cancer [10,11,[25][26][27]. It has also been reported that the upregulation of MAFG-AS1 in lung adenocarcinoma tissues is associated with adverse prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Five fields (× 200) were randomly selected under the inverted microscope (XDS-800D, Caikon Optical Instrument Co., Ltd., Shanghai, China). The number of cells that crossed the chamber membrane was counted [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs), a group of non-coding RNA longer than 200 nucleotides, have attracted research attention considering their roles as oncogenes or anti-tumor genes in the pathogenesis of CRC for diagnosis methods and treatment modalities [ 5 , 6 ]. LncRNA MAF BZIP Transcription Factor G Antisense RNA 1 (MAFG-AS1) has been reported to function in multiple types of cancer, including hepatocellular carcinoma, lung adenocarcinoma, breast cancer, and non-small cell lung cancer through interplay with different microRNAs (miRNAs) [ 7 10 ]. To our best knowledge, there is only one report discussing the action of lncRNA MAFG-AS1 in CRC, where Cui et al .…”
Section: Introductionmentioning
confidence: 99%
“…. A recent study by Ouyang et al 24 indicated that the levels of MAFG-AS1 were increased in hepatocellular carcinoma specimens and cell lines. In their in vitro assays, the knockdown of MAFG-AS1 was demonstrated to inhibit the proliferation and metastasis of hepatocellular carcinoma cells via sponging miRNA-6852.…”
Section: Mmp15 Axis 18mentioning
confidence: 98%